(untitled) (Agro Productividad, 2021)
Objective: Measure and characterize the fruit and vegetable waste generated during a working day in a commercial juice and fruit cocktail establishment in Pachuca, Hidalgo, Mexico, for four weeks. Design/ methodology/ approach: The total amount of fruit waste generated during a working day in a commercial juice and smoothie establishment in Pachuca, Hidalgo, Mexico, was collected Monday through Saturday for four weeks in September and October 2019. Waste was weighted and separated daily into the different types of fruit. We then analyzed their dry matter (DM), crude protein (CP), and ash (Ash) content. The experimental design was completely randomized. Results: The amount of fruit and vegetable waste was constant during the four collection weeks; the total amount of waste collected was 465 kg; orange peel was the most abundant waste (75%). The moisture content ranged from 75 to 94% based on the type of fruit. The CP concentration ranged from 4.33 to 6.95%, except for the papaya peel, which had a CP content of 11.55%. Limitations/ implications: An alternative to avoid landfilling this type of organic waste is to subject it to a silage-making process; this would reduce negative 2 environmental impacts, generate value-added products, and reduce the pressure on natural resources. Findings/ conclusions: The amount of fruit and vegetable waste produced every week was constant for four weeks. Although their dry matter content is low, these wastes, mixed with cereal straw and subjected to a silage-making process, can result in value-added products, and avoid landfilling.